Respuesta :
Answer:
Velocity: [tex]v(t) = 18t^{2} - 36t - 54[/tex]
The velocity equals 0 at [tex]t = 3[/tex]
Acceleration: [tex]a(t) = 36t - 36[/tex]
Step-by-step explanation:
The velocity is the derivative of the position
The acceleration if the derivative of the velocity
The position is given by the following equation
[tex]s(t) = 6t^{3} - 18t^{2} - 54t[/tex]
So the equation for the velocity is:
[tex]v(t) = 18t^{2} - 36t - 54[/tex]
Where does the velocity equal zero? [Hint: factor out the GCF.]
This is when [tex]v(t) = 0[/tex].
So
[tex]v(t) = 0[/tex]
[tex]18t^{2} - 36t - 54 = 0[/tex]
The greatest common factor between 18,36 and 54 is 18. So, factoring by 18
[tex]t^{2} - 2t - 3 = 0[/tex]
How we find the roots of a quadratic function?
Given a second order polynomial expressed by the following equation:
[tex]ax^{2} + bx + c, a\neq0[/tex].
This polynomial has roots [tex]x_{1}, x_{2}[/tex] such that [tex]ax^{2} + bx + c = (x - x_{1})*(x - x_{2})[/tex], given by the following formulas:
[tex]x_{1} = \frac{-b + \sqrt{\bigtriangleup}}{2*a}[/tex]
[tex]x_{2} = \frac{-b - \sqrt{\bigtriangleup}}{2*a}[/tex]
[tex]\bigtriangleup = b^{2} - 4ac[/tex]
So
[tex]t^{2} - 2t - 3 = 0[/tex]
[tex]a = 1, b = -2, c = -3[/tex]
[tex]\bigtriangleup = b^{2} - 4ac = (-2)^{2} -4*1*(-3) = 16[/tex]
[tex]t_{1} = \frac{-(-2) + \sqrt{16}}{2} = 3[/tex]
[tex]t_{2} = \frac{-(-2) - \sqrt{16}}{2} = -1[/tex]
We do not have a negative instant of time, so the velocity equals 0 at [tex]t = 3[/tex]
Find a function for the acceleration of the particle.
[tex]v(t) = 18t^{2} - 36t - 54[/tex]
[tex]a(t) = 36t - 36[/tex]
The function for the velocity is [tex]v(t)=18t^2-36t-54[/tex].
The velocity is zero at t = 3 and t = -1
The function for acceleration is [tex]a(t)=36t-36[/tex].
a) To find the function for velocity we'll find the first derivative of the distance function s(t).
[tex]v(t)=\frac{d}{dt}s(t)\\ \\v(t)= \frac{d}{dt}(6t^3-18t^2-54t)\\\\v(t)=6(3t^2)-18(2t)-54(1)\\\\v(t)=18t^2-36t-54\\\\[/tex]
b) We set the velocity equal to 0 and solve for t.
[tex]18t^2-36t-54=0\\18(t^2-2t-3)=0\\18(t-3)(t+1)=0\\[/tex]
We set each factor equal to 0 and solve for t.
[tex]t-3=0\\t=3[/tex]
and
[tex]t+1=0\\t=-1[/tex]
c) To find acceleration we differentiate v(t).
[tex]a(t)=\frac{d}{dt} (18t^2-36t-54)\\a(t)=18(2t)-36(1)-0\\a(t)=36t-36[/tex]
Learn more: https://brainly.com/question/18720896